Call procedure of ISDN signalling / Mohd Shuhari Zakariya @ Zakaria - Zakariya @ Zakaria, Mohd Shuhari (2003)
This project describes the Digital Subscriber Signalling No.l (DSSl) signalling in Integrated Services digital Network (ISDN). The simulation was done using Visual Basic 6.0 software and it involves the DSSl layers (layer 1 through layer 2). From this simulation, the ISDN signalling activities can be viewed easier when a call connection is made compare to an ordinary way such as figures and tables. User will then be able to understand the signalling activities from the starting call connection to the end of conversation.